Hubungan Kesadaran Metakognitif dengan Hasil Belajar IPA Biologi - Gita Ismarani; Jamaluddin; I Putu Artayasa; Kusmiyati (Journal of Classroom Action Research, 2023)
The purpose of this study was to determine the relationship between metacognitive awareness and Biology Science learning outcomes at MTs Negeri 2 Jonggat and how much the ability of metacognitive skills contributes to Biology Science learning outcomes for high school students. This research is a correlational research. Measuring students' metacognitive awareness was carried out using the Metacognitive Awareness Inventory questionnaire. Student learning outcomes seen from the results of multiple choice test questions. Data analysis in this study used descriptive analysis and statistical analysis through product moment correlation tests and simple regression tests. The results of the data analysis showed that 47 students (47.4%) had metacognitive awareness in the very good category, 44 students (44.4%) had metacognitive awareness in the good category and 8 students (8.0%) had metacognitive awareness in the medium category. Analysis of learning outcomes data showed that 84 students (84.8%) were in the very low category, 13 students (13.1%) were in the less category and 2 students (2.0%) were in the very high category. Product moment correlation test results obtained a correlation coefficient (r) of 0.146 and a coefficient of determination (r2) of 2.1%. These results indicate that there is a correlation between metacognitive awareness and Biology science learning outcomes.